Means of reader’s mind control in the political discourse(based on the vestimentary description in Spanish press) - Юлия Сливчикова (Ибероамериканские тетради)
The article considers the vestimentary description as a tool of public opinion manipulation in terms of the Spanish political discourse. The study sets out to show the mechanism of connotative meanings formation based on the neutral vocabulary that describes the public person’s dress.